The intercultural caring-coping patterns of disaster-displaced families in temporary shelters - Gallego, Randy Ian Ferenal; Balabagno, Araceli Ocampo (International Journal of Public Health Science (IJPHS), 2024)
This integrative research review sought to explore the concepts of caring and coping in the context of the disaster-displacement phenomenon. It intended to describe and characterize the process of human flourishing amidst crisis through the caring and coping experiences of people living temporarily in emergency shelters after having been forcefully displaced following a devastating disaster event. This review adopted the 11-step method introduced by Tawfik and his colleagues in 2019. Three databases were utilized which included CINAHL, PubMed, and ProQuest. Papers needed to be published in English, with full-text availability for their inclusion. A total of 16 references met the inclusion criteria for the final review. To construct a logical and coherent integration of the important points, four categories of themes were developed: i) disaster impacts on daily life patterns and cultural lifeways; ii) caring patterns during disaster displacement; iii) coping patterns during disaster displacement; and iv) cultural learnings for disaster-based practitioners. It was noted that despite the challenges of crises, disaster victims often recover naturally and return to their previous levels of functioning. Resilient caring-coping mechanisms enable people to flourish in adversity, with culture and traditions playing a vital role in shaping their adjustment and adaptation to current circumstances.